2017
DOI: 10.1038/s41598-017-03407-3
|View full text |Cite
|
Sign up to set email alerts
|

The miR-125a/HK2 axis regulates cancer cell energy metabolism reprogramming in hepatocellular carcinoma

Abstract: The Warburg effect is a metabolic hallmark of cancer. Tumor cells rapidly adjust their energy source to glycolysis in order to efficiently proliferate in a hypoxic environment, but the mechanism underlying this switch remains incompletely understood. Here, we show that hypoxia potently induces the down-regulation of miR-125a expression in hepatocellular carcinoma (HCC) cells and tumors. Furthermore, we demonstrate that miR-125a could decrease the production of lactate, the uptake of glucose, and the levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 48 publications
2
44
1
Order By: Relevance
“…Other evidences also favored that imatinib resistance was associated with overexpression of the MDR1 gene in tumor cells [143,144]. Consistently, miR-125a/HK2 axis was found to regulate the energy metabolism of hepatocellular carcinoma or squamous cell carcinoma [146,147]. Consistently, miR-125a/HK2 axis was found to regulate the energy metabolism of hepatocellular carcinoma or squamous cell carcinoma [146,147].…”
Section: Osteosarcoma and Myeloid Leukemiamentioning
confidence: 69%
See 1 more Smart Citation
“…Other evidences also favored that imatinib resistance was associated with overexpression of the MDR1 gene in tumor cells [143,144]. Consistently, miR-125a/HK2 axis was found to regulate the energy metabolism of hepatocellular carcinoma or squamous cell carcinoma [146,147]. Consistently, miR-125a/HK2 axis was found to regulate the energy metabolism of hepatocellular carcinoma or squamous cell carcinoma [146,147].…”
Section: Osteosarcoma and Myeloid Leukemiamentioning
confidence: 69%
“…In addition, UCA1 also conferred the resistance of adriamycin, a chemotherapy drug used for the treatment of AML, by sponging the miR-125a targeting HK2 to promote glycolysis [145]. Consistently, miR-125a/HK2 axis was found to regulate the energy metabolism of hepatocellular carcinoma or squamous cell carcinoma [146,147].…”
Section: Osteosarcoma and Myeloid Leukemiamentioning
confidence: 91%
“…49 HK2 has been previously identified as a target of miR-125a in laryngeal squamous cell carcinoma 50 and hepatocellular carcinoma. 51 Rescue experiments demonstrated that UCA1 overexpression overturned miR-125-mediated inhibition on HIF-1α-dependent glycolysis in HL60 and HL60/ADR cells. Collectively, these results demonstrated that knockdown of UCA1 suppresses chemoresistance of pediatric AML by inhibiting glycolysis through the miR-125a/HK2 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, miR‐125‐a, known to be involved in macrophage differential activation through downregulation of TNF‐α‐induced protein 3 (TNFAIP3) (Graff, Dickson, Clay, McCaffrey, & Wilson, ) and of the inflammatory transcription factor Kruppel‐like factor 13 (KLF13) (Banerjee, Cui, et al, ), has been recently found to be upregulated in reactive microglia and in extracellular vesicles (EVs) thereof (Prada et al, ). Few glycolytic enzymes, including enolase‐1 (ENO‐1), HK2 (F. Jin et al, ; C. M. Sun, Wu, Zhang, Shi, & Chen, ) and phosphofructokinase (PFK1) are miR‐125‐a validated targets (Table 1). Consistently, miR‐125‐a decreases the uptake of glucose and the production of lactate, and the levels of ATP and ROS in other cell types (F. Jin et al, ).…”
Section: Micrornas Promoting Pro‐regenerative Microglia Phenotype Andmentioning
confidence: 99%
“…Few glycolytic enzymes, including enolase‐1 (ENO‐1), HK2 (F. Jin et al, ; C. M. Sun, Wu, Zhang, Shi, & Chen, ) and phosphofructokinase (PFK1) are miR‐125‐a validated targets (Table 1). Consistently, miR‐125‐a decreases the uptake of glucose and the production of lactate, and the levels of ATP and ROS in other cell types (F. Jin et al, ). Whether the miRNA suppresses glycolysis in microglia remains to be proven.…”
Section: Micrornas Promoting Pro‐regenerative Microglia Phenotype Andmentioning
confidence: 99%